Monitoring and evaluation framework for inclusive smart cities in India. Issue 2 (17th February 2022) - Waghmare, Madhurima; Singhal, Shaleen
ABSTRACT: Urban investments in India over the past three decades have helped its cities advance in terms of improved infrastructure and better economic standards. However, the cities are simultaneously facing challenges of polarised and unequally distributed development benefits. This paper advances the inclusive cities' agenda beyond the constructs of "pro-poor development" and develops a multidimensional evaluation and monitoring framework. Through the review and analysis of 20 smart cities in India, the paper presents the gaps and patterns of relationships within the critical factors of inclusion. The need to develop alternate development models that shall promote socio-economic transformation in smart cities in India is emphasised through this paper.